Strategi Pembentukan Karakter Religius Peserta Didik Melalui Jaringan Online di Masa Pandemi Covid-19: Studi Kasus Di Madrasah Tsanawiyah Negeri 16 Jombang - Amalana, Arina; Badrus; Rahman, Marita Lailia (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2022)
This study aims to determine how moral knowing, moral feelings or loving the good), and moral action in the formation of the religious character of students through online networks during the Covid-19 pandemic. This study uses a qualitative approach, with primary data sources, namely the results of interviews with source person, secondary sources in the form of photos related to research activities. The data analysis technique uses data reduction, presentation and verifivation. The results of this study indicate that: through the stage of moral knowledge can make students have personal characteristics with religius character shahihul ibadah, salimul aqidah, matinul khuluq, mutsaqqoful fikri, mujahadatul linafsihi and qodirun alal kasbi, cognitive development as an elaboration of the fathanah nature of the prophet. Moral feelings can form the characteristics of students with religious character salimul aqidah, matinul khuluq, qowiyyul jismi, nafi’un lighoirihi and mujahadatul linafsihi, this affective development as a description of the attitude of the prophet’s mandate. The moral behavior or moral action of students becomes personal with religious characteristics such as mutsaqqoful fikri, matinul khuluq munazhzhamun fi syuunihi, harishun ala waqtihi, qowiyyul jismi and nafi’un lighorihi, is the role of the nature of tabligh as one of the morals of the prophet.